Foraging Behaviours and Population Dynamics of Arctic Foxes - Samelius, G. (ARCTIC, 2004)
. The main objectives of my work are to examine (1) how arctic foxes use seasonally abundant foods and (2) how seasonal and annual fluctuations in food abundance affect foraging behaviours and population dynamics of arctic foxes. I am especially interested in how arctic foxes use geese and their eggs (i.e., seasonally abundant foods) and how this varies with fluctuations in small mammal abundance (i.e., foods that fluctuate annually). . My work is done at Karrak Lake (67°14'N, 100°16'W) and surrounding areas in the Queen Maud Gulf Bird Sanctuary in Nunavut, Canada. . Fieldwork for my project was done in the spring and summers of 2000-04, and data analyses are currently underway. I monitor population dynamics of arctic foxes in two goose nesting areas at Karrak Lake and two areas outside the influence of nesting geese, whereas I monitor foraging behaviours of arctic foxes in one section of the goose colony at Karrak Lake. . I examine foraging behaviours of arctic foxes by observing individually marked foxes with spotting scopes . Avoiding cache loss to competitors is a critical component for the evolution of caching . I examine how nesting distribution of geese and dispersal of geese away from the colony affect cache loss by evaluating the survival rate of experimentally deployed caches . I examine arctic fox diets by comparing isotope ratios (delta 13C and delta 15N) of fox tissues . with those of food items collected in the field . Fur is metabolically inactive, whereas blood is metabolized continuously ., so by examining spring blood and winter fur I obtain information on both spring and fall diets. Geese are not present at Karrak Lake in either spring or fall, so goose signatures in this study represent foods cached in summer. I monitor population dynamics of arctic foxes . through line-transect surveys, mark-recapture studies, and den inventories. . Goose eggs (from both nests and existing caches) made up 91% of all foods taken by arctic foxes during goose-nesting at Karrak Lake. Foxes cached 96% of these ...